Five per cent measurements of the growth rate from simulation-based modelling of redshift-space clustering in BOSS LOWZ. Issue 2 (28th October 2021) - Lange, Johannes U; Hearin, Andrew P; Leauthaud, Alexie; van den Bosch, Frank C; Guo, Hong; DeRose, Joseph
ABSTRACT: We use a simulation-based modelling approach to analyse the anisotropic clustering of the BOSS LOWZ sample over the radial range 0.4 h^-1 Mpc to 63 h^-1 Mpc, significantly extending what is possible with a purely analytic modelling framework. Our full-scale analysis yields constraints on the growth of structure that are a factor of two more stringent than any other study on large scales at similar redshifts. We infer f σ8 = 0.471 ± 0.024 at z ≈ 0.25, and f σ8 = 0.430 ± 0.025 at z ≈ 0.40; the corresponding ΛCDM predictions of the Planck cosmic microwave background (CMB) analysis are 0.470 ± 0.006 and 0.476 ± 0.005, respectively. Our results are thus consistent with Planck, but also follow the trend seen in previous low-redshift measurements of f σ8 falling slightly below the ΛCDM + CMB prediction. We find that small- and large-radial scales yield mutually consistent values of f σ8, but there are 1−2.5σ hints of small scales (10 h^-1 Mpc ) preferring lower values for f σ8 relative to larger scales. We analyse the constraining power of the full range of radial scales, finding that most of the multipole information about f σ8 is contained in the scales 2 h^-1 Mpcs 20 h^-1 Mpc . Evidently, once the cosmological information of the quasi-to-nonlinear regime has been harvested, large-scale modes contain only modest additional information about structure growth. Finally, we compare predictions for the galaxy–galaxy lensing amplitude of the two samples against measurements from SDSS and assess the lensing-is-low effect in light of our findings.